Isolated Lumbar Extension Resistance Training Improves Strength, Pain, and Disability, but Not Spinal Height or Shrinkage ("Creep") in Participants with Chronic Low Back Pain. (April 2020) - Steele, James; Bruce-Low, Stewart; Smith, Dave; Jessop, David; Osborne, Neil
Objective . Loss of disc height is commonly associated with chronic low back pain (CLBP). Isolated lumbar extension (ILEX) exercise for the lumbar extensors is recommended to treat CLBP and is suggested such exercise might promote disc healing and regeneration. This study examined a 12-week ILEX intervention on indirect determination of disc height and shrinkage through seated stadiometry, strength, pain, and disability. Design . A quasi-experimental wait-list controlled design was used. Nine participants underwent pretesting (T1), a 12-week control period, retesting (T2), a 12-week intervention period, and finally posttesting (T3). Seated stadiometry, ILEX strength, pain, and disability were measured at each time point. Results . No significant repeated-measures effects for any seated stadiometry variables occurred. Significant improvement across the intervention period (T2 to T3) was found for strength ( P <0.0001; effect size [ES] = 2.42). Change in pain was not significant for repeated effects ( P = 0.064); however, ES for the intervention period (T2 to T3) was moderate (ES = −0.77). Change in disability was significant between time point T1 and T3 ( P = 0.037) and ES for the intervention period (T2 to T3) was large (ES = −0.92). Pain and disability achieved minimal clinically important changes. Conclusions . This is apparently the first study to examine disc change in vivo after exercise in CLBP. Results of the present study, though supporting ILEX resistance training to improve strength, pain, and disability, did not find any effect on spinal height.